2015
DOI: 10.1246/cl.150005
|View full text |Cite
|
Sign up to set email alerts
|

Apatite/Polymer Composite Materials with Fractal Rough Surfaces

Abstract: We prepared an apatite/polymer composite material with a fractal surface by transferring the hierarchical rough surface of a plaster replica onto calcium phosphate paste and immersing the paste in a buffer. The rough structure (fractal dimension: 2.3) accelerated the spreading and penetration of a water droplet placed on the surface. This material can be applied in dental implants and texture testers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Apatite is reported to be formed more easily on surfaces of chemically treated titanium and organic polymers with microasperity due to more favorable surface energy with respect to heterogeneous apatite nucleation. 15), 16) We found that heterogeneous nucleation of apatite occurred with high probability following pretreatment with an alkali solution of appropriate concentration.…”
Section: Effect Of Titanium Coating and Alkali Treatmentmentioning
confidence: 89%
“…Apatite is reported to be formed more easily on surfaces of chemically treated titanium and organic polymers with microasperity due to more favorable surface energy with respect to heterogeneous apatite nucleation. 15), 16) We found that heterogeneous nucleation of apatite occurred with high probability following pretreatment with an alkali solution of appropriate concentration.…”
Section: Effect Of Titanium Coating and Alkali Treatmentmentioning
confidence: 89%